Bioinspired Activation of N2 on Asymmetrical Coordinated Fe Grafted 1T MoS2 at Room Temperature†. Issue 7 (30th May 2021) - Guo, Jiaojiao; Wang, Maoyu; Xu, Liang; Li, Xiaomin; Iqbal, Asma; Sterbinsky, George E.; Yang, Hao; Xie, Miao; Zai, Jiantao; Feng, Zhenxing; Cheng, Tao; Qian, Xuefeng
Main observation and conclusion: Inspired by the nitrogen fixation process on MoFe nitrogenase, asymmetrical coordinated Fe grafted onto 1T MoS2 were successfully synthesized. The unique electron‐rich structure with asymmetrical coordination made the 1T Fe0.1 Mo0.9 S2 layered material actively react with water and dinitrogen at room temperature and atmosphere pressure. Subsequently, ammonia can be produced with a yield of ~800 μmol (NH4 + ) g −1 (12.5% yield in mole). The activation, fixation and reduction of dinitrogen were confirmed by isotopically labeled experiments. The location and the specific coordination environment of grafted Fe in Fe‐Mo‐S were further determined by X‐ray absorption spectroscopy analysis. Our work demonstrates that the nitrogen fixation and reduction for ammonia at room temperature without any chemical and electrochemical assistance is distinctly different from traditional bionic‐inspired nitrogen fixation process. The mechanism of the activation and reduction of N2 was further investigated by density functional theory calculation and Raman spectra. Compared with 1T MoS2, the enriched electron nature and asymmetrical coordination of Fe in Fe‐Mo‐S materials play a critical role in the bioinspired activation of N2 at ambient condition. Abstract : The electron‐rich asymmetrical coordinated Fe grafted onto 1T MoS2 can activate dinitrogen and react with water to form ammonia (12.5% yield in mole) at room temperature and atmosphere pressure.